3358 Developmental Outcomes of Aicardi Goutieres Syndrome - Adang, Laura (J Clin Transl Sci, 2019)
OBJECTIVES/SPECIFIC AIMS: Metachromatic leukodystrophy (MLD) is a rare, lysosomal storage disorder caused by decreased enzymatic activity of arylsulfatase A. This can be the result of mutations in the ASA gene, or in rare cases PSAP. Historically, MLD has been subdivided into 3 forms based on age of onset: late infantile, juvenile, and adult. These subtypes were defined decades ago, prior to the appreciation of the full clinical spectrum of this lysosomal storage disorder and the advent of genetic testing. As a consequence, these empiric age-based historical definitions do not fully account for the spectrum of disease and are not founded in evidence-based analysis of phenotypic cohorts. Additionally, the antiquated definitions do not fully predict presenting features or disease course, and they fail to stratify outcomes in the few therapies currently available to treat this disease. As novel targeted therapeutics are developed, it is essential to have a clear understanding of the clinical presentation and natural history of MLD. Without properly defined sub-populations, it is difficult to design a therapeutic clinical trial that can demonstrate efficacy in a heterogeneous group. METHODS/STUDY POPULATION: In this project, we collected the retrospective natural history of over 50 individuals from around the world. We created an electronic database in REDCap to able to longitudinally collect clinical information. Using this retrospective natural history approach to understanding the disease course of individuals affected by MLD, we were able to characterize age of onset, delay to diagnosis, and common presenting features. RESULTS/ANTICIPATED RESULTS: Our results suggest distinct clinical phenotypic subgroups, with distinct presentations. DISCUSSION/SIGNIFICANCE OF IMPACT: With a better understanding of the natural history of MLD, we will be able to better counsel families and to design clinical trials with more coherent cohorts and more appropriate clinical endpoints.